2010
DOI: 10.1063/1.3485825
|View full text |Cite
|
Sign up to set email alerts
|

Extended and localized surface plasmons in annealed Au films on glass substrates

Abstract: We present here a study on the surface plasmon resonance (SPR) in Au films deposited onto glass substrates and annealed in air at different temperatures. The initial Au films exhibit the resonant absorption of extended surface plasmons which depends on the film thickness. Thermal treatments promote the modification of the continuous films toward the formation of Au isolated islands. The morphological features of the islands depend on the film initial thickness and annealing temperature. The optical properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 25 publications
10
77
0
1
Order By: Relevance
“…The RMS increased to 48.1 nm. This effect is similar to the roughening observed in annealed Au thin films [9,10]. AFM measurements performed on the nanostructures supported by the asdeposited gold substrate revealed that in most cases the carbon nanodisks are not completely flat.…”
Section: Resultssupporting
confidence: 65%
“…The RMS increased to 48.1 nm. This effect is similar to the roughening observed in annealed Au thin films [9,10]. AFM measurements performed on the nanostructures supported by the asdeposited gold substrate revealed that in most cases the carbon nanodisks are not completely flat.…”
Section: Resultssupporting
confidence: 65%
“…94 Therefore, we focus our study on the effect of initial thickness and annealing temperature. 12 In AFM images, we could observe that all as-grown films presented a continuous structure, while after annealing Au films exhibited a discontinuous structure with a similar Grain size distribution results very broad, with grains in the range from 100 to 400 nm.…”
Section: Morphological Characterization Of Samplesmentioning
confidence: 84%
“…Concretamente, para películas con espesores menores de 30 nm, las nanoestructuras obtenidas tras el tratamiento térmico exhiben LSPs mientras que para las películas con espesores mayores, las islas de Au son lo suficientemente grandes (dimensiones más grandes que la longitud de onda de la luz visible) y ESPs pueden ser excitados. 12 Por otro lado, para el caso de las bicapas Au/Fe,éstas son crecidas sobre substratos de sílice bajo diferentes configuraciones y posteriormente son tratadas térmicamente en aire o bajo vacío, bajo diferentes condiciones del tratamiento. Los tratamientos térmicos de bicapas suponen un nuevo método de fabricación de nano y microestructuras complejas que es presentado aquí por primera vez.…”
Section: Introductionunclassified
See 2 more Smart Citations